If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 6x + 13 Reorder the terms: 4x = 13 + 6x Solving 4x = 13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = 13 + 6x + -6x Combine like terms: 4x + -6x = -2x -2x = 13 + 6x + -6x Combine like terms: 6x + -6x = 0 -2x = 13 + 0 -2x = 13 Divide each side by '-2'. x = -6.5 Simplifying x = -6.5
| 2/5x+1=-23 | | X=3ln(x) | | 8x-9=24 | | (x^2-4x+5)/(x-2) | | 6y-0.6=7y | | 2(4+2y)+5y=17 | | r-6.5=-6.8 | | y=1.3x-4.7 | | 5-9-8/-9+9 | | 5(4x-7)-4(x+2)-18x= | | 24+3n=3(n+8) | | 2.8(3r+9)-1.5r= | | 3/5(x+4)+1/2x=x+3 | | 4y+4-8y-1= | | 8y-1-4y+4= | | 00.5X+10=-0.05x+70 | | 200x-51=49 | | -4(1+8k)+8k=-24-4k | | (2x+5)-(7x+1)= | | (7x+1)-(2x+5)= | | 7x+1-2x+5= | | 7d=58+9d | | (8x-8)-(6x-10)= | | 4x=-(3/16) | | 4/x+7/x^2-2/x^3 | | 8x-8-6x-10= | | =3z(8-5z) | | 6x-4+5x+3= | | 9+3ab+-1ab+-4=0 | | -6(5x-3y+4)= | | 3xh+9x= | | y=3x^2-x+20 |